Ethics and politics in the theatre of Hélène Cixous - Williams, Martina (2017)
This thesis explores ethics and politics in Hélène Cixous’s theatre, and shows that rich and complex analyses of ethical and political questions lie at the heart of Cixous’s plays. Although they regularly attract large audiences, her plays remain relatively understudied. This thesis therefore contributes towards closing a significant gap in Cixous scholarship and in scholarship of recent French theatre.